The human gut fungiome: Role in physiology and detoxification - Gilles-Eric Seralini (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2023)
The intestinal microbiota is an ecosystem where bacteria, archaea, viruses, and protists, are entangled, but not alone. We take microbiota as the bacterial community because, in many historical papers, the probes to detect other organisms in the intestine were rarely used. But in addition, unicellular fungi or yeasts do exist in microbiota, their assembly is called the mycome or fungiome, and it can reach the size and number of our human cells. The bacteria are far more numerous. For a long time, the whole was taken for a nest of pathogens, but in fact, yeasts adapted and evolved as symbiotic cells helping not only our digestion, but also angiogenesis, tissue growth, vitamin synthesis, and our nervous, endocrine, immune systems and even our detoxification system. Much of what we swallow is or will become fermented, like bread, cheese, or wine. Since the beginning of agriculture, our food is eaten lightly by microbiota including yeasts first in plants not treated by pesticides. Natural yeasts still unknown are in hundreds of types or species at the very least, bringing in particular during their work of fermentation a multiplicity of aromas that play a role in the famous detoxification; but the usual diet only provides a few strains of these yeasts. In yeasts like in all cells, ubiquitous cytochrome P450 detoxifying enzymes form a vast family also involved in cell respiration, which is stimulated to some extent by the aromas and other signals secreted. Yeasts could attract and coordinate bacteria to eliminate in part chemical pollutants.